Growth differentiation factor-5–gelatin methacryloyl injectable microspheres laden with adipose-derived stem cells for repair of disc degeneration. (31st December 2020) - Xu, Haibin; Sun, Miao; Wang, Chenggui; Xia, Kaishun; Xiao, Shining; Wang, Ye; Ying, Liwei; Yu, Chao; Yang, Quanming; He, Yong; Liu, An; Chen, Linwei
Abstract: Nucleus pulposus (NP) degeneration is the major cause of degenerative disc disease (DDD). This condition cannot be treated or attenuated by traditional open or minimally invasive surgical options. However, a combination of stem cells, growth factors (GFs) and biomaterials present a viable option for regeneration. Injectable biomaterials act as carriers for controlled release of GFs and deliver stem cells to target tissues through a minimally invasive approach. In this study, injectable gelatin methacryloyl microspheres (GMs) with controllable, uniform particle sizes were rapidly biosynthesized through a low-cost electrospraying method. The GMs were used as delivery vehicles for cells and GFs, and they exhibited good mechanical properties and biocompatibility and enhanced the in vitro differentiation of laden cells into NP-like phenotypes. Furthermore, this integrated system attenuated the in vivo degeneration of rat intervertebral discs, maintained NP tissue integrity and accelerated the synthesis of extracellular matrix. Therefore, this novel therapeutic system is a promising option for the treatment of DDD.